1986
DOI: 10.1002/eji.1830161004
|View full text |Cite
|
Sign up to set email alerts
|

Immune serum from mice contact‐sensitized with picryl chloride contains an antigen‐specific T cell factor that transfers immediate cutaneous reactivity

Abstract: This report describes an activity in serum from mice that were contact-sensitized with picryl chloride (PCl) 1 to 4 days earlier. Immune serum, when given i.v., transfers the ability to elicit an immediate hypersensitivity-like ear swelling reaction in naive recipients following local challenge with PCl. This serum activity is due to an antigen-binding T cell factor that shares some properties with IgE antibody. The activity is antigen specific, and due to an antigen-binding moiety that is heat labile (56 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…and perhaps mast cells [7]. We employed induction of suppression of DTH with Ag-binding factors from the contact sensitivity system to examine whether the early allo-MHC-specific component of DTH was required for elicitation of DTH, and might thus be involved in immune resistance to an allograft tumor.…”
Section: Allograft Dth and Allograft Tumor Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…and perhaps mast cells [7]. We employed induction of suppression of DTH with Ag-binding factors from the contact sensitivity system to examine whether the early allo-MHC-specific component of DTH was required for elicitation of DTH, and might thus be involved in immune resistance to an allograft tumor.…”
Section: Allograft Dth and Allograft Tumor Immunitymentioning
confidence: 99%
“…We have shown that DTH-initiating cells make Ag-specific DTH-initiating fac tors that we call, respectively: picryl chloride factor (PCI-F), and oxazolone factor (OX-F) [5,6,10,24]. These factors are not IgE anti bodies [6,7,9,10], nor are they dependent on IgE antibodies [10] UV tumor Ag-specific T cells were not able to transfer DTH, nor resistance to tumors. However, when combined with 1-day im mune DTH-initating cells of the Ag specific ity appropriate to a particular U V tumor, the specific DTH-initiating cells and the specific T cell line together were able to mediate immune resistance to the appropriate tumor [29].…”
Section: Dth Initiation Is Important In Variousmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparent support for this proposal derives from evidence that reserpine, a drug that depletes mast cells of serotonin, markedly inhibits the elicitation of contact hypersensitivity [24,25], It has been further suggested that the early and late phases of dermal hypersensitivity reactions to contact allergens are, in the mouse, effected by the sequential action of two indepen dent antigen-specific populations of T lymphocytes [23,26]. The T lymphocyte responsible for inducing the early inflammatory response is considered to have a distinctive phenotype, and to produce an antigen-binding factor that sensitizes tissue mast cells in the manner of IgE [27][28][29][30][31], Following challenge, antigen is thought to bind to such sensitized mast cells, initiate degranulation and allow the infiltration of the second population of T lymphocytes that cause the late phase reaction [28,29], The concept of a mandatory requirement for early phase inflammation during the development of delayed hypersensitivity reactions remains controversial, however. It has been found, for instance, that mast cell-deficient mice exhibit delayed dermal hypersensitivity reactions comparable with those observed in normal animals [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonality of TABM analogous to immunoglobulins is suggested by charge hetero geneity [8]; but the non-MHC-restricted TABM demonstrate similar characteristics [5,8,21]. TABM can be isolated from serum of sensitized mice [29] and are found on the surface of T cells, as well as in supernatants of lymphoid cell cultures [7,21,31] and display common serologic determinants [6,7], sug gesting a common isotype among antigen-specific T cell factors.…”
Section: Introductionmentioning
confidence: 99%